2017
DOI: 10.1177/1555412017698872
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Break or Permanent Departure? Rethinking What It Means to Quit EVE Online

Abstract: To date, much of the research about massively multiplayer online games (MMOGs) and the people who play them has focused on studies of current players. Comparatively, little is known about why players quit. Rather than assuming MMOG play begins and ends with personal interest, this article uses a leisure studies framework to account for barriers and participation to play. Drawing on survey responses from 133 former EVE Online players, this article demonstrates that quitting is not a strict binary where one move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
6
13
0
Order By: Relevance
“…School and work were present among the reasons for not currently playing, consistent with previous literature investigating similar matters (Bergstrom, 2017(Bergstrom, , 2015. However, likely in part due to the demographic differences of this participant pool as compared to earlier work about MMOGs, having children and/or domestic responsibilities were not included as a possible reason for no longer playing in these previous studies about quitting.…”
Section: Reasons For No Longer Playing Yoworldsupporting
confidence: 88%
“…School and work were present among the reasons for not currently playing, consistent with previous literature investigating similar matters (Bergstrom, 2017(Bergstrom, , 2015. However, likely in part due to the demographic differences of this participant pool as compared to earlier work about MMOGs, having children and/or domestic responsibilities were not included as a possible reason for no longer playing in these previous studies about quitting.…”
Section: Reasons For No Longer Playing Yoworldsupporting
confidence: 88%
“…However, they may still maintain social ties with current players who would encounter a recruitment post and pass it along to former players in their social circles via other channels (email, social media, etc.). Therefore we suggest taking a similar approach to recruitment like we have here, and in our prior work [3]. By building a branching survey that can accommodate answers from current, former, and non-players, and then specifically including in the recruitment text that participants should forward the survey to people they know who have quit gaming, it will ultimately increase the number of former players completing the survey.…”
Section: Implications For the Recruitment Of Former Players In Futurementioning
confidence: 99%
“…[30:11] While we recognize that the magic circle is a contested concept within the broad field of game studies [16], Dutton's provocation that the person who withdraws from a game may speak more readily about the taken for granted norms and expectations of a particular community is still useful. Indeed, in our previous work we have found that former players are candid about the barriers and hostility preventing full participation in a particular gameworld, while current players tend to be focused on maintaining the exclusivity and mystique associated with the same game [3,5]. Despite the insights they offer, former players are often a missing perspective in the study of the social aspects of digital gameplay, in large part due to the difficulty of identifying them during the recruitment stage of the research process.…”
Section: Introductionmentioning
confidence: 97%
“…EVE ’s notorious (Bergstrom & Carter, 2015) reputation for thefts and scams is not the outcome of its rules and coded design (e.g., see Warmelink, 2013), but it is coconstructed by players and developers over time. This is why studying elements like EVE ’s tutorial, which demands players seek assistance from the game’s community (Bergstrom, 2013; Paul, 2012, 2015), how the cultures of its communities are established (Milik & Webber, 2017), the cultural differences in EVE play (Page, 2017), and players who have “quit” EVE (Bergstrom, 2017) offer significant insight into how and where EVE ’s moral economy is established and the role participatory fan cultures play in this process.…”
Section: Conclusion: On Studying Moral Economiesmentioning
confidence: 99%